(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Acute pancreatitis is an acute inflammatory condition of the pancreas with a clinical spectrum ranging from mild self-limiting disease to severe pancreatitis associated with multiorgan dysfunction and mortality. Early prediction of disease severity is essential for appropriate management. Serum interleukin-6 (IL-6) and ferritin have emerged as potential early biomarkers of severity and prognosis. Objectives: To evaluate the role of serum IL-6 and serum ferritin as prognostic markers in acute pancreatitis and compare their predictive value with established scoring systems such as Ranson score and CT Severity Index (CTSI). Materials and Methods: This prospective observational analytical study was conducted in the Department of Surgery, Dr. D. Y. Patil Medical College Hospital and Research Institute, Kolhapur, over a period of two years. Patients aged 18–70 years presenting within 48 hours of onset of first-episode acute pancreatitis were included. Clinical assessment, laboratory investigations including serum amylase, lipase, IL-6, ferritin, LDH, ABG, and BUN, along with radiological evaluation by ultrasonography and contrast-enhanced CT, were performed. Ranson score and CTSI were calculated and correlated with disease severity. Results: Mild acute pancreatitis was the most common presentation. Increasing severity was significantly associated with higher Ranson scores, CT severity scores, LDH, serum lipase, IL-6, and ferritin levels (p<0.0001). SIRS at admission, ICU admission, local complications, and CT evidence of necrosis were significantly associated with severe disease. Mean IL-6 and ferritin levels increased progressively from mild to severe pancreatitis, demonstrating strong correlation with disease severity and adverse clinical outcomes. Conclusion: Serum IL-6 and ferritin are valuable early prognostic biomarkers in acute pancreatitis and correlate strongly with disease severity. Combined with Ranson score and CT Severity Index, these markers facilitate early risk stratification, timely intervention, and improved clinical outcomes.